2019
DOI: 10.1111/eci.13079
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic fat and aerobic fitness are key determinants of glucose homeostasis in nonobese Asians

Abstract: Background The importance of ectopic fat deposition and physical fitness in the pathogenesis of insulin resistance and beta cell dysfunction in subjects from the nonobese Asians is not known. Materials and methods We conducted a cross‐sectional study and measured insulin sensitivity (M value; 4‐hour hyperinsulinaemic‐euglycaemic clamp), insulin secretion rate (3‐hour mixed meal tolerance test with oral minimal modelling), percent body fat, visceral adipose tissue, intramyocellular and intrahepatic lipid conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…This is mainly brought about by reduction in the pancreatic and hepatic fat content (37) . Presence of fat at ectopic sites is now considered as a key driver connecting adiposity with T2DM and other cardiometabolic disorders (38,39) .…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly brought about by reduction in the pancreatic and hepatic fat content (37) . Presence of fat at ectopic sites is now considered as a key driver connecting adiposity with T2DM and other cardiometabolic disorders (38,39) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the IMAT volume was inversely proportional to aerobic physical fitness quantified based on total treadmill duration [34]. A previous study of non-obese Asians revealed that VF and intrahepatic triglycerides (IHTGs), which were measured using magnetic resonance spectroscopy, were inversely correlated to insulin sensitivity [35] and that VF and IHTGs were inversely proportional to CRF (VO 2 max/BW). These results suggest that the deposition of ectopic fat might be suppressed in individuals with high CRF and high VF levels.…”
Section: Discussionmentioning
confidence: 97%
“…While the mechanistic interplay between low CRF, MAFLD, and T2D remains unclear, it is purported that the incomplete oxidation of fatty acids in the mitochondria may contribute to the build-up of fatty acid by-products, such as ceramides and diacylglycerol intracellularly, which impair insulin signalling pathways and mitochondrial function and may contribute to, or be the result of, low CRF [38,39]. Importantly, T2D-related exercise intolerance appears to be reversed by structured exercise and is made evident by the amelioration of mitochondrial impairments, increased mitochondrial content, improved insulin sensitivity, decreased IHL and increased CRF [15,16,40,41].…”
Section: Bivariate Correlationsmentioning
confidence: 99%